Splenic Abscess: A Rare Complication of the UVC in Newborn - Ameer Aslam; Emad Sadek Ahmed Shatla; Sameera Imanullah; Elsaid M. A. Bedair (Hindawi Limited, 2014)
Splenic abscess is one of the rarest complications of the UVC in a newborn and it is hypothesized that it could be due to an infection or trauma caused by a catheter. The case that is being reported presented with abdominal distension and recurrent desaturation with suspicion of neonatal sepsis versus necrotizing enterocolitis. However, the final diagnosis was splenic abscess as a complication of an inappropriate UVC insertion which was discovered by abdominal ultrasound. The patient was given broad spectrum antibiotics empirically and the symptoms were resolved without any surgical intervention. Such cases and controlled studies need to be reported in order to identify further causes and risk factors associated with splenic abscess in a patient with UVC which can eventually help us adopt preventive strategies to avoid such complications.